2023
DOI: 10.1037/hea0001263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a video-based positive side-effect information framing: An online experiment.

Abstract: Objective: Despite the public health value of vaccines, vaccination uptake rates are stagnating. Expected adverse events following immunization are a major source of concern and play a role in the emergence of vaccine hesitancy. Since nocebo mechanisms are involved in the perception of adverse reactions, positive side-effect communication is warranted. The aim of the present study was to compile a comprehensive communication strategy that minimizes expectations of nocebo effects while respecting the informed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Although nocebo phenomena have been investigated in many contexts involving medication, evidence of their influence in vaccination remains scarce. However, a recent meta-analysis suggested that a significant proportion of placebo recipients in influenza vaccine trials experienced systemic AEs, such as headache or fatigue, owing to nocebo responses …”
Section: Introductionmentioning
confidence: 99%
“…Although nocebo phenomena have been investigated in many contexts involving medication, evidence of their influence in vaccination remains scarce. However, a recent meta-analysis suggested that a significant proportion of placebo recipients in influenza vaccine trials experienced systemic AEs, such as headache or fatigue, owing to nocebo responses …”
Section: Introductionmentioning
confidence: 99%
“…Delporte et al (2023) assessed the impacts of optimism and moral appeals on vaccine intention. Bender et al (2023) conducted a four-arm randomized study, with presentation of standard information about vaccine side effects versus enhanced messaging using a positively framed message, each for COVID-19 vaccine and influenza vaccine. This message focused both on the probability of not having a side effect postvaccination and on referring to side effects as signs that the immune system is activating.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…The promotion focus had a stronger association with vaccination intention and uptake than did the prevent focus. This included seeking earlier vaccination (e.g., through trying to get leftover doses when available), in line with the positive framing effects documented by Bender et al (2023).…”
Section: Overview Of the Special Issuementioning
confidence: 99%
See 2 more Smart Citations